MINERAL NUTRIENT STATUS OF SOME MEDITERRANEAN BARLEY VARIETIES AS AFFECTED BY DROUGHT STRESS IN EGYPT - & et al., Hellal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Field experiment was carried out at the experimental research station of Nubaria, representing the newly reclaimed sandy loam soils of Egypt. The study was done to evaluate the nutrient status of barley varieties (Egyptian, Tunisian, Algerian and Morocco) grown under normal (75% water holding capacity=WHC) and stress condition (40% WHC). Results indicated that the Egyptian variety El-Arish scored the highest values of N% under normal and drought stress condition and Giza 127 for P and Giza 123 for K in same sequence. The lowest values of N, P and Ca content observed with Giza 2000 variety. As for the Tunisian varieties, the lowest reduction percentage was attained at Raihane (9.38%, 3.54% and 3.62%) for N, K and Ca, respectively. Algerian barley varieties, N in Naïlia/Techedrett, P in Temacine/Ksar Megrine, K in Ras El-Mouche/Temacine, Ca in Saida/Ksar Megrine, got the highest and lowest values under normal and stress conditions, respectively. Morocco varieties, lowest values of N, P, K and Ca were recorded for Massine, Taffa and Amalou under water stress condition. The highest and lowest value of Fe, Zn and Mn were recorded for barley varieties Giza 2000, Giza 131 and Giza 127, respectively. Results concluded that the Egyptian varieties (Giza 127, Giza131, Giza 2000), Tunisian varieties (Kebili-3 and Tozeur-2), Algerian varieties (Techedrett, Naïlia) and Morocco varieties (Laanaceur, Amira) registered the lowest reduction percentage in nutrient content indicating their tolerance to sustain its productivity under water stress condition.